Simulation and manufacturing of modified circular monopole microstrip antenna for UWB applications - Bilal S. Taha; Hamzah M. Marhoon (Institute of Advanced Engineering and Science, 2021)
Ultra-wideband (UWB) technology is one of the most promising wireless communication solutions to be developed quickly because of the high-speed data, wide bandwidth and excellent immunity to multipath interference. In this work, the compact design of a modified circular monopole microstrip antenna is simulated and manufactured for the UWB applications. The simulation process of the proposed antenna was done based on the finite integration of the computer simulation technology (CST) microwave studio (MWS). The proposed antenna comprises a copper radiating patch, Roger’s Kappa-438 substrate, and a single stub act as a reflector. The simulation results showed a reasonable agreement with the results of the measurement and good performance was achieved in the range from 1.8 to 10 GHz with VSWR less than 2.0.